KEANEKARGAMAN KUPU-KUPU DIURNAL (SUB ORDO: RHOPALOCERA) DI KOMPLEK GUNUNG BROMO KPH SURAKARTA KABUPATEN KARANGANYAR TAHUN 2013 - Hariyatmi Hariyatmi; Rofi Safi’i Ahmad Susetya (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The purpose of this study is to determine the diversity of diurnal butterflies (Sub Order : Rhopalocera) in complex Mount Bromo KPH Karanganyar Surakarta in 2013. Research is explorative quantitative research done by analyzing the value of the Shannon diversity index and evenness of species in the population. Sampling was done by catching butterflies directly on the 4 pieces that have been deemed most representative of the entire complex regional characteristics and vegetation of Mount Bromo. Sampling results obtained in stage 4 for 211 individuals consisting of 4 familia, 21 genera and 26 species . Analysis showed diversity with Shannon index H 'value of 2.249 at stage 1 ; 2,558 at stage 2 ; 2,664 to 2,218 at stage 3 and stage 4 . While the value of H ' for all the research stage is 2,956 butterfly diversity means there is the category of being . The distribution of species in the study sites can be said to be evenly distributed with the value of E = 0.907 . Keywords : butterfly, mount bromo, diversity